2015
DOI: 10.1155/2015/418681
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Cysteine and Tyrosine: Early Biomarkers in Asymptomatic Adults at Increased Risk of Developing Metabolic Syndrome

Abstract: As there is effective intervention for delaying or preventing metabolic diseases, which are often present for years before becoming clinically apparent, novel biomarkers that would mark metabolic complications before the onset of metabolic disease should be identified. We investigated the role of fasting serum amino acids and their associations with inflammatory markers, adipokines, and metabolic syndrome (MetS) components in subjects prior to the onset of insulin resistance (IR). Anthropometric measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 55 publications
2
40
1
1
Order By: Relevance
“…Therefore, serum Cys imbalances correlate with markers of metabolic dysfunction. We found significant positive correlations between serum Cys and HOMA-IR, CRP, TNF-α, WC and body shape index in recent work [28], and here we present a significant positive correlation between Cys and TAC.…”
Section: Gendersupporting
confidence: 84%
“…Therefore, serum Cys imbalances correlate with markers of metabolic dysfunction. We found significant positive correlations between serum Cys and HOMA-IR, CRP, TNF-α, WC and body shape index in recent work [28], and here we present a significant positive correlation between Cys and TAC.…”
Section: Gendersupporting
confidence: 84%
“…In contrast to several adult studies which related BCAA to IR and obesity [42,46,47] , the results in children are rather inconsistent. Some studies found BCAA or BCAA-associated factors to be related with obesity [48][49][50][51][52] or even predictive for later IR [52] or triglyceride levels [53] in childhood.…”
Section: Childhoodcontrasting
confidence: 65%
“…Both studies showing beneficial effects of BCAA were published by the same group and conducted in the same collective. The authors state that the contrast of their beneficial findings of BCAA in adolescents and other studies showing adverse associations in adults, may be due to the adaptive (mitochondrial) mechanisms which are still present in youth but vanish with the progression of obesity [42,46,47] .…”
Section: Childhoodmentioning
confidence: 85%
“…However, abnormal levels of Cys are associated with a number of health problems, including cancer, neurological disorders, and motor neuron diseases. [123][124][125][126][127] Therefore, the development of an analytical tool for the detection of Cys over other thiol-containing biologically important species is highly desirable.…”
Section: Cysteine (Cys)mentioning
confidence: 99%